Discriminación salarial por género en Chile: Una mirada global - Fuentes, Jeanette; Montero, Rodrigo; Palma, Amalia (Estudios de Economía, 2016)
Using data from the CASEN survey, this paper analyzes the evolution of gender wage discrimination in Chile over the period 1990-2003. The methods of Oaxaca- Blinder and Oaxaca and Ransom were implemented to investigate whether there is wage discrimination. The estimations were corrected using selection bias and bootstrapping techniques were used to construct intervals of confidence. The results suggest that although gender wage discrimination decreased during the period, it still remained and issue. In fact, in 2003 this was around 27.5%, which corresponds to an average under-payment to women of 14.3%, and to an average over-payment to payment to men of 13.2%.